The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/b978-0-12-416618-9.00005-4
|View full text |Cite
|
Sign up to set email alerts
|

Techniques to Monitor Glycolysis

Abstract: An increased flux through glycolysis supports the proliferation of cancer cells by providing additional energy in the form of ATP as well as glucose-derived metabolic intermediates for nucleotide, lipid, and protein biosynthesis. Thus, glycolysis and other metabolic pathways that control cell proliferation may represent valuable targets for therapeutic interventions and diagnostic procedures. In this context, the measurement of glucose uptake and lactate excretion by malignant cells may be useful to detect shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
194
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(196 citation statements)
references
References 48 publications
(56 reference statements)
2
194
0
Order By: Relevance
“…Qualitative analysis of glycolysis determined by the extracellular acidification rate (ECAR) was markedly repressed in DKO platelets (Figure 1E). Of note, ECAR was not zero in DKO platelets potentially reflecting acidification of the media, by acids other than lactate (TeSlaa and Teitell, 2014). Consistent with studies in human platelets (Karpatkin, 1968), thrombin increased glycolysis by ~2-fold in control murine platelets.…”
Section: Resultsmentioning
confidence: 99%
“…Qualitative analysis of glycolysis determined by the extracellular acidification rate (ECAR) was markedly repressed in DKO platelets (Figure 1E). Of note, ECAR was not zero in DKO platelets potentially reflecting acidification of the media, by acids other than lactate (TeSlaa and Teitell, 2014). Consistent with studies in human platelets (Karpatkin, 1968), thrombin increased glycolysis by ~2-fold in control murine platelets.…”
Section: Resultsmentioning
confidence: 99%
“…S5D, E). Extracellular flux analysis measures the rate of acidification of the medium and is an indicator of glycolytic flux [51]. We observed that TNBC cells have higher extracellular flux (ECAR) indicative of higher glycolysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ϫ/Ϫ adipocytes exhibited elevated nonglycolytic acidification (ECAR after 2-deoxyglucose [2-DG] treatment) produced by the acidification of CO 2 , the end product of the tricarboxylic acid cycle (47). The addition of glucose increased ECAR in Bscl2 ϩ/ϩ brown adipocytes, and more so in cells deficient in Bscl2, suggesting a greater ability to increase glycolysis.…”
Section: Bscl2mentioning
confidence: 99%